Antimicrobial peptides (AMPs) of lizards: a first comprehensive characterization of beta-defensins, ovo-defensins and cathelicidins from Podarcis lilfordi and closely related Lacertidae species - Katherin Otalora; Jessica Gómez-Garrido; Laura Baldo (BMC Genomics)
Abstract Background Reptiles exhibit remarkable resistance to infections, making them a critical model for studying the molecular basis of innate immunity. Key components of their innate immune response are the antimicrobial peptides (AMPs), small, rapidly evolving molecules with a broad spectrum of antimicrobial activity. Despite their importance, AMPs in reptiles remain largely understudied, with no current studies available on one of the most successful reptilian lineages, lizards from the Lacertidae family. In this study, we performed an extensive mining of published Lacertidae genomes and present the first comprehensive characterization of their major AMP families —beta-defensins (BDs), ovo-defensins (OVODs), and cathelicidins (CATHs) — with the aim of understanding their genomic diversity and evolution. Results We first identified a nearly complete catalogue of antimicrobial proteins from Podarcis lilfordi, an endemic lizard of the Balearic Islands (Spain): this included 63 BDs, eight OVODs, three of which are proline-rich proteins (OVOD-PrAMPs), and four CATHs. These AMPs are arranged in chromosome clusters of mostly contiguous peptides, flanked by highly conserved marker proteins. Using this fine-scale annotation, we mined corresponding orthologues and closed paralogues from P. muralis, P. raffonei and Zootoca vivipara, identifying a total of 58 AMPs. All AMPs consistently locate on chromosome 3 (BDs and OVODs) and chromosome 12 (CATHs), supporting a monophyletic origin for the reptilian antimicrobial defense. All Lacertidae AMPs show a multiple exon structure (two to four exons) and a characteristic cysteine motif (six cysteines in BDs, eight in OVODs, and four in CATHs), consistently with previous findings for vertebrates. Comparative sequence analyses indicate pervasive duplication events in tandem of both BDs and OVODs, with clear evidence of recent gene expansion. In contrast, OVOD-PrAMPs and CATHs mostly present a one-to-one ortholog across species. Despite this high level of intra-genomic diversity, we also identified multiple instances in which different species from distantly related Squamata families (Lacertidae, Varanidae and Dactyloidae) share identical or nearly identical peptides, suggesting convergent evolution. Conclusions Overall, our findings support a remarkable diversity of AMPs in lizards, driven by an ongoing process of gene expansion, primarily via duplication in tandem, and rapid diversification. The observed instances of peptide identity or similarity, along with the putative maintenance of specific polymorphisms across species, provide a basis for investigating the potential functional equivalence of these peptides among lizards and underscore the need for population-level studies of allele intraspecific diversity.